Health Promotion Behavior of the Elderly in Rural areas after Mudslides at Namlee village, Namman subdistrict, Thapla district, Uttaradit Province - Muangkaew, Prapaporn; Mahayosnan, Pavimon (NU Journal of Nursing and Health Sciences, 2020)
This research aimed to study the Health promotion behavior of the elderly in rural areas after mudslides at Namlee village, Namman subdistrict, Thapla district, Uttaradit Province. Studied in sixty-two elderly population aged 60 and over who were able to perform daily activities and lived in Namlee village during the mudslide disaster in 2006. Data were collected by using structured interview form that were interviewed on health promotion behaviors of the elderly ,based on Pender’s Health Promotion Behavior Framework (Pender, 2006). Content validity testing by using experts and reliability testing by using Cronbach’s Alpha Coefficient was at .83. Quantitative data analysis were used, frequency,percentage, mean and standard deviation The results showed that elderly health promotion behaviors were at a good level. (μ = 3.69, σ = 0.60). The most highest score of elderly health promotion behaviors was a dimension of Nutrition ( =4.14 , =1.41) and subsequently dimension was relationship (μ = 4.12, σ = 0.65) at a high level. The lowest score of health promotion behaviors was a dimension of activities and exercise (μ = 3.09 , σ = 0.86) and subsequently dimension was mental development. (μ = 3.50, σ = 0.85) at a medium level. Suggestion that Bannamlee Health Promotion Hospital and authorities’ network related health should urgently promote and support elderly to have more activities and exercise, and mental development.